The Influence of Pricing and Location on Purchase Decisions at Carrefour Transmart - Triyadi Triyadi; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Peneliti.net, 2022)
This study was conducted with the aim to determine the effect of price fixing on purchasing decisions at Transmart Carrefour Tangerang Center, to determine the effect of location on purchasing decisions at Transmart Carrefour Tangerang Center, and to determine the effect of pricing and location on purchasing decisions at Transmart Carrefour Tangerang Center. This study uses quantitative research methods with a descriptive approach. Quantitative Research is a research method based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, data analysis is quantitative/statistical, with the aim of testing established hypotheses. Based on the results of the study, the t-value of 4.069 > 1.96 means that the organizational climate has a positive and significant effect on employee performance. This means that if the organizational climate has increased, the performance of employees will also increase. The path coefficient is 0.232, which means that the contribution of the influence of organizational climate to employee performance is 23.2% and the remaining 76.8% are other factors not investigated